2017
DOI: 10.4314/ijbcs.v10i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Floristic and structural changes in secondary forests following agricultural disturbances: the case of Lama forest reserve in Southern Benin

Abstract: Structural changes in secondary forests are less known in West Africa, and this precludes their management. This study aims at providing quantitative information on floristic composition and structure of the Lama secondary forests (Benin), so as to contribute to their restoration, and fill part of knowledge gaps on West African secondary forests. Data of 77 permanent plots each of 0.5 ha were used to analyze the floristic composition, the trajectory of the recovery and the recovery of stocking in these forests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…The majority of this forest have been extensively degraded in other to pave ways for other land uses such as industrial estate, crop fields and/or plantations (Prance et al, 2000). The degradation of forest ecosystem is usually accompanied by species extinction, reduction in biodiversity and decrease in primary productivity (Martínez-Ramos et al, 2016;Gbetoho et al, 2017). Currently, an estimated 850 million hectares of degraded forests exist globally.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of this forest have been extensively degraded in other to pave ways for other land uses such as industrial estate, crop fields and/or plantations (Prance et al, 2000). The degradation of forest ecosystem is usually accompanied by species extinction, reduction in biodiversity and decrease in primary productivity (Martínez-Ramos et al, 2016;Gbetoho et al, 2017). Currently, an estimated 850 million hectares of degraded forests exist globally.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary forests are growing in many parts of the world due to anthropic disturbances, but the issue of their management and restoration to primary forest is of great concern because the critical knowledge to guide that management is lacking (Makana and Thomas, 2008;Gbètoho et al, 2016). Depending on the level of degradation, Lamb (1994) suggested that reforestation may be done through substitution of the natural forest by plantation, rehabilitation, restoration or natural succession.…”
Section: Introductionmentioning
confidence: 99%
“…Les valeurs des indices de diversité des différents biotopes de la forêt de Badenou sont inférieures à celles des différents biotopes de la forêt classée de Bamo obtenues par (Adingra, 2017). Toutes ces valeurs sont synonymes d'un manque de stabilité de la flore des différents biotopes du site (Adingra, 2017 (Kassi et al 2011 ;Adingra, 2017 ;N'Guessan et al 2019 Gbètoho et al (2016) qui montraient que les compositions floristiques sont généralement rattachées à la diversité des habitats. Ces travaux montrent que la végétation des jachères les plus âgées (30 ans et plus) est relativement proche de celle rencontrée dans les forêts anciennes.…”
Section: Indices De Diversité Floristiqueunclassified